2018
DOI: 10.1021/acs.cgd.8b01425
|View full text |Cite
|
Sign up to set email alerts
|

Solvate Formation of Bis(demethoxy)curcumin: Crystal Structure Analyses and Stability Investigations

Abstract: Bis(demethoxy)curcumin (BDMC), extracted from rhizomes of the traditional herb Curcuma longa, has revealed a wide range of medicinal applications, such as antimicrobial and anticarcinogenic. Pure BDMC was obtained by recrystallization from ethanol and three BDMC solvates were identified with acetone, methanol and isopropanol. The crystal structures of pure BDMC and the solvates were resolved by single crystal X-ray diffraction. Analyses of the crystal structures and calculations of crystal packing efficiencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…Through the identification of robust supramolecular synthons, it is possible to select suitable coformers for co-crystallization. BDMC can exist in the β-diketone and the keto-enol form (Figure 2a) whereas only the keto-enol form can be found in crystal structures due to its higher stability [31]. With its hydroxyl, carbonyl and phenyl functional groups the following supramolecular synthons can be identified (Figure 2b): The second approach for selecting suitable coformers is based on structural resemblance to a well investigated molecule and was first introduced by Springuel et al [38].…”
Section: Selection Of Coformersmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the identification of robust supramolecular synthons, it is possible to select suitable coformers for co-crystallization. BDMC can exist in the β-diketone and the keto-enol form (Figure 2a) whereas only the keto-enol form can be found in crystal structures due to its higher stability [31]. With its hydroxyl, carbonyl and phenyl functional groups the following supramolecular synthons can be identified (Figure 2b): The second approach for selecting suitable coformers is based on structural resemblance to a well investigated molecule and was first introduced by Springuel et al [38].…”
Section: Selection Of Coformersmentioning
confidence: 99%
“…In a patent 6 co-crystals with piperazine, caffeine, L-proline, nicotinamide, isonicotinamide and piperidine are reported but not fully proved [ 26 ]. The formation of BDMC solvates was investigated extensively by Yuan et al [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis explaining this behavior might be incorporation of small amounts of respective alcohol molecules in the crystal structure without changing the structure type. Further, according to the known complex solid phase behavior of CUR [42][43][44][45][46][47][48] and BDMC [49,50], also the formation of a new metastable form of CUR in the three alcohols or a solvate phase from ethanol are possible explanations. Since elucidation of the CUR phase behavior was not the main focus of the present study, this issue has to be verified in future investigations.…”
Section: Selection Of Solvents For Crystallizationmentioning
confidence: 99%
“…The engagement of the solvent molecules could compensate the original vacancy of interaction force such as the imbalance of hydrogen bonds, halogen bonds, and π–π stacking, etc., [ 9,18 ] while the incorporation of solvent molecule into the gaps of the crystals would also make a more efficient packing mode, thus further affecting the stability of solvate crystals. [ 19 ] With the development of analytical technique and computer simulation technology, [ 20,21 ] researchers have made great progress in the study of intermolecular interactions on the stability of solvates. [ 2,13,22 ] For example, Yuan et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,13,22 ] For example, Yuan et al. [ 19 ] studied the effect of intermolecular interaction on solvate formation of bis(demethoxy)curcumin (BDMC). It was suggested that a stronger hydrogen bond network would lead to a more stable BDMC‐MeOH solvate.…”
Section: Introductionmentioning
confidence: 99%